Graphene/layered double hydroxides nanocomposites: A review of recent progress in synthesis and applications. (August 2016) - Daud, Muhammad; Kamal, Muhammad Shahzad; Shehzad, Farrukh; Al-Harthi, Mamdouh A.
Abstract: Hybrids of graphene (G) and layered double hydroxides (LDHs) are promising nanomaterials due to their versatile properties and the large number of composition/preparation variables available for fine-tuning. Several techniques are available for the synthesis of these novel G/LDHs nanocomposites. This article reviews the recent developments in their synthesis and applications in the oxygen evolution reaction, supercapacitors, hybrid sensors, adsorption, catalysis, water purification, and flame retardant materials.